PENGUATAN MANAJEMEN SYARIAH MELALUI TOTAL QUALITY MANAGEMENTBAGI PELAKU LEMBAGA KEUANGAN SYARIAH DI KOTA SEMARANG - Arifin, Johan (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2016)
One of the problems that arise in the Islamic financial management is the governance model (management) used are the same as a conventional financial institution management in general, Therefore we need innovation in management. Management Implementation of Sharia in the Islamic financial institutions are expected to improve the performance and quality of these institutions. Implementation of sharia management really comes down to the issue of Total Quality Management (TQM) on financial institutions syar'iah focused on the process of continuous improvement to uphold the values of Shariah.Management of sharia is considered important in the company since its implementation in the areas of services and operating in personal competence, maintaining the availability of knowledge and innovation as well as product development. Through sharia management is expected to increase the skills and motivation to work on giliranyya will improve the reinforcement of the operational side. The perpetrator of Islamic financial institutions in terms of technical skills are adequate but the problem is the knowledge of the management of sharia. Knowledge management in Islamic financial institutions will be judged by the public that the management is not different from the conventional financial institutions.